β2 Integrin Signaling Cascade in Neutrophils: More Than a Single Function - Bouti, Panagiota; Webbers, Steven D. S.; Fagerholm, Susanna C.; Alon, Ronen; Moser, Markus; Matlung, Hanke L.; Kuijpers, Taco W. (Frontiers in Immunology, 2021)
Neutrophils are the most prevalent leukocytes in the human body. They have a pivotal role in the innate immune response against invading bacterial and fungal pathogens, while recent emerging evidence also demonstrate their role in cancer progression and anti-tumor responses. The efficient execution of many neutrophil effector responses requires the presence of β2 integrins, in particular CD11a/CD18 or CD11b/CD18 heterodimers. Although extensively studied at the molecular level, the exact signaling cascades downstream of β2 integrins still remains to be fully elucidated. In this review, we focus mainly on inside-out and outside-in signaling of these two β2-integrin members expressed on neutrophils and describe differences between various neutrophil stimuli with respect to integrin activation, integrin ligand binding, and the pertinent differences between mouse and human studies. Last, we discuss how integrin signaling studies could be used to explore the therapeutic potential of targeting β2 integrins and the intracellular signaling cascade in neutrophils in several, among other, inflammatory conditions in which neutrophil activity should be dampened to mitigate disease.